2016
DOI: 10.1177/1756283x16638833
|View full text |Cite
|
Sign up to set email alerts
|

Predicting durable response or resistance to antitumor necrosis factor therapy in inflammatory bowel disease

Abstract: Monoclonal antibodies to tumor necrosis factor (TNF) have become a mainstay of the therapeutic armamentarium in inflammatory bowel disease (IBD) over the last 15 years. Although highly effective, primary and secondary nonresponse are common and associated with poor clinical outcomes and significant costs. Multiple clinical, genetic and immunopharmacological factors may impact the response to anti-TNFs. Early stratification of IBD patients by the expected risk of therapeutic failure during the induction and mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 121 publications
3
64
0
1
Order By: Relevance
“…Several previous studies have linked a deleterious clinical outcome among infliximab therapy IBD patients with longer disease duration, smoking, older age, previous IBD‐related surgeries and elevated baseline CRP . A recent study by Papamichael and colleagues demonstrated that older age, BMI and previous surgery were associated with primary nonresponse .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have linked a deleterious clinical outcome among infliximab therapy IBD patients with longer disease duration, smoking, older age, previous IBD‐related surgeries and elevated baseline CRP . A recent study by Papamichael and colleagues demonstrated that older age, BMI and previous surgery were associated with primary nonresponse .…”
Section: Discussionmentioning
confidence: 99%
“…Primary nonresponse to infliximab therapy occurs in 10%‐30% of IBD patients . The mechanisms underlying this phenomenon are still obscure, and it is estimated that primary nonresponse can be either a pharmacokinetic process (in the presence of low drug and elevated ATI levels) or a pharmacodynamic one (with sufficient drug levels and no ATI, hence probably not TNF driven) .…”
Section: Discussionmentioning
confidence: 99%
“…It may be that the patients who require more lines of therapy are more resistant to treatment due to factors such as genetics, age, and duration of disease. 9 Null et al 6 found that approximately half of patients receiving infliximab or adalimumab discontinued from the biologic treatment during the first 12 months, and that a substantial percentage of these patients were not restarted on or switched to a biologic therapy. These data correspond with our results: 54% and 55% of patients with UC and CD, respectively, remained on the index biologic therapy at 12 months, and a substantial percentage were switched to a nonbiologic (eg, 5-ASA or CS) in the second line.…”
Section: Discussionmentioning
confidence: 99%
“…The development of antibodies to anti-TNF agents is the most common reason for loss of response to this treatment, 183 and it occurs to some extent in almost 60% of patients with IBD within three years. 184 Most, although not all, studies show an inhibition of antibody formation and an increase of active drug levels with the concomitant use of thiopurines or methotrexate, 73 although clinical benefits are not universally demonstrable, especially if the previous antimetabolite therapy had been unsuccessful.…”
Section: Immune Reactionsmentioning
confidence: 99%